Hubungan Self-Confidence Dan Hasil Belajar Matematika Peserta Didik Kelas VIII SMP N 9 Pontianak - Nafa Salsabila; Hamdani; Mohamad Rifat; Pasaribu, Revi Lestari (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to determine whether there is a relationship between self-confidence and student mathematics learning outcomes. This kind of study can be called a quantitative descriptive conducted at SMPN 9 Pontianak. The population in this study was class VIII students, the research sample, namely class VIII D students, was 30 students. The data collected are the results of learning tests in the form of mathematical description problems and self-confidence questionnaires. Based on processed data assisted by Microsoft Excel and SPSS 16 by applying tests for correlation of product moments the results of the analysis data are descriptive. Based on the research findings, it can be said that learning outcomes in mathematics and student confidence are interrelated with a correlation of 0.877. That way it can be concluded that the level of self-confidence that students have correlates with the results of learning mathematics. Keywords:  learning outcomes, mathematics learning, self-confidence